2008
DOI: 10.1007/s00268-008-9675-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Allogeneic Red Blood Cell Transfusion in Ampullary Cancer Outcome after Curative Pancreatoduodenectomy: A Clinical Study and Meta‐Analysis

Abstract: The amount of intraoperative ABT is one of the important factors that adversely influenced survival in patients with ampullary cancer after curative pancreatoduodenectomy. Healing anemia preoperatively and careful dissection to minimize intraoperative bleeding as much as possible are mandatory for reducing risk of the intraoperative ABT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 64 publications
5
36
0
1
Order By: Relevance
“…Interestingly, a preoperative hemoglobin value of less than 11 g/dl was OR odds ratio, CI confidence interval, CRI chronic renal insufficiency also a risk factor for early PPH, which should be taken into account in the preoperative workup and optimization of the patient's clinical condition before PD. This is in line with recent findings where intraoperative red blood cell transfusions adversely influenced long-term survival in patients undergoing pancreatic resection for ampullary cancer [18,19]. Intraoperative transfusion during pancreatoduodenectomy was also identified as a significant risk factor for the need of postoperative extended ICU stay [20].…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, a preoperative hemoglobin value of less than 11 g/dl was OR odds ratio, CI confidence interval, CRI chronic renal insufficiency also a risk factor for early PPH, which should be taken into account in the preoperative workup and optimization of the patient's clinical condition before PD. This is in line with recent findings where intraoperative red blood cell transfusions adversely influenced long-term survival in patients undergoing pancreatic resection for ampullary cancer [18,19]. Intraoperative transfusion during pancreatoduodenectomy was also identified as a significant risk factor for the need of postoperative extended ICU stay [20].…”
Section: Discussionsupporting
confidence: 82%
“…A long-term follow-up study (mean survival 49 months) of 67 patients who underwent pancreatoduodenectomy for carcinoma found that transfusion of 3 or more units of allogeneic red cells was associated with significantly poorer median (25 months) and cumulative 3-year and 5-year survivals (36.7 and 30.2%) than those of patients transfused with 2 units and/or nontransfused patients and was an independent poor prognostic factor (RR 2.082, 95% CI 1.48-4.315; P ¼ 0.036) [55].…”
Section: Blood Transfusionmentioning
confidence: 95%
“…In particular, reported transfusion rates for pancreaticoduodenectomy range from 20% to 75% [1][2][3][4]. The high frequency of pRBCs transfusion is not unexpected due to the length of the procedure as well as the intimate relationship between the pancreatic head and major vascular structures.…”
mentioning
confidence: 98%